Acute Kidney Injury Biomarkers Predict an Increase in Serum Milrinone Concentration Earlier Than Serum Creatinine–Defined Acute Kidney Injury in Infants After Cardiac Surgery. Issue 2 (April 2018) - Gist, Katja M.; Cooper, David S.; Wrona, Julia; Faubel, Sarah; Altmann, Christopher; Gao, Zhiqian; Marino, Bradley S.; Alten, Jeffrey; Hock, Kristal M.; Mizuno, Tomoyuki; Vinks, Alexander A.; Joy, Melanie S.; et al.
Abstract : Background: Milrinone, an inotropic agent used ubiquitously in children after cardiac surgery, accumulates in acute kidney injury (AKI). We assessed if urinary AKI biomarkers are predictive of an increase in milrinone concentrations in infants after cardiac surgery. Methods: Multicenter prospective pilot study of infants undergoing cardiac surgery. Urinary AKI biomarkers were measured in the urine at specific time intervals after cardiopulmonary bypass initiation. AKI was defined using the Kidney Disease: Improving Global Outcomes serum creatinine criteria. Serum milrinone concentrations were measured at specific intervals after drug initiation, dose changes, and termination. Excessive milrinone activity was defined as a 20% increase in serum concentration between 6 and 36 hours after initiation. The temporal relationship between urinary AKI biomarker concentrations and a 20% increase in milrinone concentration was assessed. Results: AKI occurred in 31 (33%) of infants. Milrinone clearance was lower in patients with AKI (4.2 versus 5.6 L/h/70 kg; P = 0.02). Excessive milrinone activity was associated with development of serum creatinine–defined AKI [odds ratio (OR) 3.0; 95% confidence interval (CI), 1.21–7.39; P = 0.02]. Both tissue inhibitor metalloproteinase type 2 and insulin-like growth factor–binding protein type 7 (TIMP-2*IGFBP-7) ≥0.78 at 12 hours (OR 2.72; 95% CI, 1.01–7.38; P = 0.04) and kidney injury molecule 1 (KIM-1) ≥529.57 at 24 hours (OR 2.76; 95% CI, 1.06–7.17; P = 0.04) predicted excessive milrinone activity before a diagnosis of AKI. Conclusions: In this pilot study, urine TIMP-2*IGFBP-7 and KIM-1 were predictive of AKI and excessive milrinone activity. Future studies that include a pharmacodynamics assessment of patient hemodynamics, excessive milrinone activity, and AKI biomarker concentrations may be warranted to integrate this concept into clinical practice.